A PROCESS-GENRE BASED APPROACH TO TEACHING WRITING REPORT TEXT TO SENIOR HIGH SCHOOL STUDENTS (a case study) - Pujianto, dimas (2013)
Penelitian ini menginvestigasi apakah pendekatan process-genre berkontribusi terhadap kemampuan menulis teks Report siswa program studi IPA di satu sekolah negeri di Bandung. Studi ini bertujuan untuk mengeksplorasi apakah tahapan pengajaran pada pendekatan process-genre membantu siswa meningkatkan kemampuan menulis teks Report dilihat dari struktur skematik dan ciri kebahasaan yang dimiliki teks Report serta mengidentifikasi tanggapan siswa terhadap pendekatan process-genre dalam kemampuan menulis teks Report. Untuk mendapatkan hasil yang diinginkan, disain penelitian deskriptif dengan menggunakan karakteristik studi kasus diterapkan (Merriam, 1988; Nunan, 1992; Cresswell, 2012). Data diperoleh dari observasi kelas (observasi awal dan proses pembelajaran menggunakan pendekatan process-genre), analisis produk tulisan siswa, dan wawancara kepada siswa. Kerangka dasar dari pendekatan process-genre secara praktik adalah sintesis dari tahapan pengajaran pendekatan genre-based dan process-based (Badger & White, 2000; Yan, 2005; Lee, et al. 2009; Emilia, 2010). Untuk menganalisis produk tulisan siswa, enam teks dari tiga siswa yang mewakili kategori prestasi dianalisis berdasarkan struktur skematik dan ciri kebahasaan teks Report yang diturunkan dari kerangka SFL GBA (Linguistic and Education Research Network, 1990; Martin, 1992; Gerot & Wignell, 1994; Halliday, 1994; Martin, Mathiessen, & Painter, 1997; Anderson & Anderson, 1997; Christie, 2005; Feez & Joyce, 2006; Hyland 2007; Emilia, 2012). Penelitian ini menunjukkan bahwa, pada aspek tertentu, pendekatan process-genre sangat membantu untuk mengembangkan kemampuan siswa dalam menulis teks Report dilihat dari struktur skematik dan ciri kebahasaannya. Selain itu, data dari wawancara ditemukan bahwa sebagian besar siswa terbantu oleh tahapan pengajaran dalam pendekatan process-genre, khususnya dalam hal pengetahuan genre, proses menulis yang dilakukan, dan feedback dari teman sebaya dan guru. Namun, studi ini mengidentifikasi pula bahwa siswa dengan pencapaian di bawah rata-rata membutuhkan tahapan modelling dan teacher-conference yang lebih panjang untuk membantu meningkatkan kemampuan menulis mereka. Hasil dari penelitian ini diharapkan mampu memberikan kontribusi dalam memperkaya penelitian yang terkait tentang implementasi pendekatan process-genre untuk pengajaran menulis di Indonesia. Selain itu, diharapkan pula memberikan pemahaman bagi para guru dalam penerapan pendekatan process-genre dengan penekanan terhadap tahap modelling bagi siswa dengan pencapaian di bawah rata-rata dan menggunakan pendekatan untuk pengajaran jenis teks dan keterampilan berbahasa lainnya karena masih sejalan dengan kurikulum Bahasa Inggris di Indonesia. Pada akhirnya, sehubungan dengan penemuan studi ini, diharapkan para guru mendapatkan informasi mengenai cara mengatasi masalah yang berhubungan implementasi pendekatan process-genre di kelas EFL di Indonesia. Kata Kunci: Menulis, Pendekatan Process-based, Pendekatan Genre-based, Pendekatan Process-Genre, Teks Report Abstract This paper investigates whether process-genre based approach contributes towards students' writing ability of Report text to one Science class of a state senior high school in Bandung. This study, thus, intends to explore whether teaching stages in process-genre based approach help students improve writing ability of Report text in terms of schematic structure and linguistic features as well as to find out students' responses towards the approach to their writing ability of Report text. To meet the purposes of the study, a descriptive research design embracing the characteristics of a single-case study was employed (Merriam, 1988; Nunan, 1992; Cresswell, 2012). The data were obtained from classroom observation (preliminary observation and learning process through process-genre based approach), students' writing products analysis, and interview with students. The basic frameworks of process-genre based approach are practically the synthesis of teaching stages in genre-based and process-based approaches (Badger & White, 2000; Yan, 2005; Lee, et al. 2009; Emilia, 2010). For analysing students' writing products, six texts from three students representing achievement categories were analysed using the analysis of schematic structure and linguistic features of Report text derived from SFL GBA frameworks (Linguistic and Education Research Network, 1990; Martin, 1992; Gerot & Wignell, 1994; Halliday, 1994; Martin, Mathiessen, & Painter, 1997; Anderson & Anderson, 1997; Christie, 2005; Feez & Joyce, 2006; Hyland 2007; Emilia, 2012). This study revealed that, to some extent, process-genre based approach was helpful to develop students' ability to write Report text in terms of schematic structure and linguistic features. In addition, from the interview, it was figured out that most students were assisted by the teaching stages in process-genre based approach, specifically on the knowledge of the genre, writing process they went through, and feedback from peers and teacher. Nevertheless, it was identified that low-achieving students needed longer modelling stage as well as teacher-conference to help improve their writing ability. The findings of this study are hoped to make contributions to enrich research about the implementation of process-genre based approach to teaching writing in Indonesia. Furthermore, it is expected to give understanding to other teachers in implementing process-genre based approach to teaching writing with more attention to modelling stage for low-achieving students as well as using the approach for other text types and skills since the approach still fits the English curriculum in Indonesia. Finally, relevant to the findings, it is hoped that teachers can get information to overcome problems related to the implementation of the approach in EFL classrooms in Indonesia. Keywords: Writing, Process-based Approach, Genre-based Approach, Process-Genre Based Approach, Report Text.